Analysis of the Level of Customer Satisfaction with Trans Binjai Transportation Services - Putri Hsb, Anisa; Barus, Elida Elfi (Journal of Management Sains (JMS), 2025)
The Binjai City Government is actively working to alleviate traffic congestion by enhancing the quality of its bus-based public transportation system. As part of this effort, the North Sumatra Provincial Transportation Office introduced 22 new Trans Binjai fleets on August 20, 2023, operating on the Binjai-Medan City route to encourage a shift from private vehicle use to public transport. This study aims to analyze passenger characteristics and evaluate their satisfaction levels with Trans Binjai services. The research employs the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) to measure service performance. Findings reveal that most Trans Binjai passengers are female (65%) and predominantly aged 18-28 years (47%). The majority have a high school education (55%) and are self-employed (40%), with a monthly income of less than Rp 2,000,000 (60%). Additionally, 70% of passengers use Trans Binjai primarily for commuting to work. The CSI analysis yielded a satisfaction score of 78%, classifying the service within the “satisfied” category. Meanwhile, IPA analysis indicates that service attributes are distributed across quadrants II and III, signifying that certain aspects require urgent attention. Specifically, safety and comfort are identified as key areas for improvement to enhance overall passenger experience. These findings highlight the need for targeted service enhancements to improve customer satisfaction and further encourage public transportation use. By addressing critical service aspects, the Binjai City Government can strengthen Trans Binjai’s role in reducing traffic congestion and promoting sustainable urban mobility.